Arctic's hidden hydrocarbon degradation microbes: investigating the effects of hydrocarbon contamination, biostimulation, and a surface washing agent on microbial communities and hydrocarbon biodegradation pathways in high-Arctic beaches - Chen, Ya-Jou; Altshuler, Ianina; Freyria, Nastasia J.; Lirette, Antoine; Góngora, Esteban; Greer, Charles W.; Whyte, Lyle G. (Environmental Microbiome, 2024)
Background: Canadian Arctic summer sea ice has dramatically declined due to global warming, resulting in the rapid opening of the Northwest Passage (NWP), slated to be a major shipping route connecting the Atlantic and Pacific Oceans by 2040. This development elevates the risk of oil spills in Arctic regions, prompting growing concerns over the remediation and minimizing the impact on affected shorelines. Results: This research aims to assess the viability of nutrient and a surface washing agent addition as potential bioremediation methods for Arctic beaches. To achieve this goal, we conducted two semi-automated mesocosm experiments simulating hydrocarbon contamination in high-Arctic beach tidal sediments: a 32-day experiment at 8 °C and a 92-day experiment at 4 °C. We analyzed the effects of hydrocarbon contamination, biostimulation, and a surface washing agent on the microbial community and its functional capacity using 16S rRNA gene sequencing and metagenomics. Hydrocarbon removal rates were determined through total petroleum hydrocarbon analysis. Biostimulation is commonly considered the most effective strategy for enhancing the bioremediation process in response to oil contamination. However, our findings suggest that nutrient addition has limited effectiveness in facilitating the biodegradation process in Arctic beaches, despite its initial promotion of aliphatic hydrocarbons within a constrained timeframe. Alternatively, our study highlights the promise of a surface washing agent as a potential bioremediation approach. By implementing advanced -omics approaches, we unveiled highly proficient, unconventional hydrocarbon-degrading microorganisms such as Halioglobus and Acidimicrobiales genera. Conclusions: Given the receding Arctic sea ice and the rising traffic in the NWP, heightened awareness and preparedness for potential oil spills are imperative. While continuously exploring optimal remediation strategies through the integration of microbial and chemical studies, a paramount consideration involves ...